Knowledge and Data Sharing - Annual Technical Report 2021 - Tobon, Hector; Almanzar, Manuel; Ramírez, Margarita M.; Tanaka, Kenji (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The main purpose of this team effort is to help the AICCRA Project to support evidencebased decision-making by ensuring that the research data, which is essential for the integrity, quality, and value of research, is appropriately managed at the cluster level. It also strengthens the culture of results-based project monitoring and evaluation (M&E) by ensuring the reporting of high-quality information products. Additionally, we support establishing data sharing and management processes from legal agreements through research operations and reporting. This “conveyor belt” process is applied to AICCRA through the MIS reporting system called Managing Agricultural Research for Learning and Outcomes (MARLO). MARLO is an online platform assisting the AICCRA project in its strategic results-based program planning and reporting of research clusters. It covers the cluster cycle from planning to reporting and learning. Reports generated by the system support outcome-focused programmatic reporting with additional synthesis at the flagship and cross-cutting levels.